The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/nchembio.1986
|View full text |Cite
|
Sign up to set email alerts
|

Correlating chemical sensitivity and basal gene expression reveals mechanism of action

Abstract: Changes in cellular gene expression in response to small-molecule or genetic perturbations have yielded signatures that can connect unknown mechanisms of action (MoA) to ones previously established. We hypothesized that differential basal gene expression could be correlated with patterns of small-molecule sensitivity across many cell lines to illuminate the actions of compounds whose MoA are unknown. To test this idea, we correlated the sensitivity patterns of 481 compounds with ~19,000 basal transcript levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
756
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 692 publications
(789 citation statements)
references
References 47 publications
33
756
0
Order By: Relevance
“…To account for these differences and determine where treatment with HDACi may be beneficial, diagnostic indicators of HDACi efficacy are needed. While several genomic approaches correlating HDACi response with mutational landscape or changes in basal gene expression serve as invaluable tools to identify prognostic markers associated with HDACi efficacy (Rees et al, 2016, Garnett et al, 2012), our study compliments this approach by identifying direct changes in HDAC binding, selectivity and enzymatic activity, which may also affect HDACi efficacy.…”
Section: Discussionmentioning
confidence: 95%
“…To account for these differences and determine where treatment with HDACi may be beneficial, diagnostic indicators of HDACi efficacy are needed. While several genomic approaches correlating HDACi response with mutational landscape or changes in basal gene expression serve as invaluable tools to identify prognostic markers associated with HDACi efficacy (Rees et al, 2016, Garnett et al, 2012), our study compliments this approach by identifying direct changes in HDAC binding, selectivity and enzymatic activity, which may also affect HDACi efficacy.…”
Section: Discussionmentioning
confidence: 95%
“…[27] Looking at gene expression profiles of breast cancer cells treated with ML239, NF-kB (nuclear factor kappa-light-chainenhancer of activated B cells), a protein complex that is implicated in transcription and cytokine production, was significantly altered. [28] It was subsequently argued that ML239 acts mainly through activation of FADS2 (fatty acid desaturase 2), [29] supporting the notion that metabolic states of CSCs can potentially be exploited for therapeutic purposes. Other classes of molecules, such as cinnamides, [15b] were also identified to target CSCs using the HMLER model, highlighting the power of unbiased approaches in the context of CSCs where little is known about a potential Achilles' heel.…”
Section: Unbiased Screening Approaches -Case-studiesmentioning
confidence: 99%
“…Natural herbal products are used in traditional medicine, and it is currently considered in anticancer activities [36], [37]. These activity indexes, apoptosis stimulation and antiproliferative activities [38], as research has shown that these natural healing products had no side effects, or as minimum side effects were much more reasonable compared with that chemotherapeutic [39].…”
Section: Discussionmentioning
confidence: 99%